Bimanual coupling paradigm as an effective tool to investigate productive behaviors in motor and body awareness impairments - Garbarini, Francesca; Pia, Lorenzo (Frontiers in Human Neuroscience, 2013)
When humans move simultaneously both hands strong coupling effects arise and neither of the two hands is able to perform independent actions. It has been suggested that such motor constraints are tightly linked to action representation rather than to movement execution. Hence, bimanual tasks can represent an ideal experimental tool to investigate internal motor representations in those neurological conditions in which the movement of one hand is impaired. Indeed, any effect on the ‘moving’ (healthy) hand would be caused by the constraints imposed by the ongoing motor program of the ‘impaired’ hand. Here, we review recent studies that successfully utilized the above-mentioned paradigms to investigate some types of productive motor behaviors in stroke patients. Specifically, bimanual tasks have been employed in left hemiplegic patients who report illusory movements of their contralesional limbs (anosognosia for hemiplegia). They have also been administered to patients affected by a specific monothematic delusion of body ownership, namely the belief that another person’s arm and his/her voluntary action belong to them. In summary, the reviewed studies show that bimanual tasks are a simple and valuable experimental method apt to reveal information about the motor programs of a paralyzed limb. Therefore, it can be used to objectively examine the cognitive processes underpinning motor programming in patients with different delusions of motor behavior. Additionally, it also sheds light on the mechanisms subserving bimanual coordination in the intact brain suggesting that action representation might be sufficient to produce these effects.